Peningkatan Kompetensi Profesional Guru melalui Pelatihan Kendali Motor Listrik berbasis Variable Speed Drive - Doni Tri Putra Yanto; Mukhlidi Muskhir; Ricky Maulana (Universitas Negeri Padang, 2022)
The Vocational High School (SMKN) 1 Sumatera Barat is one of the vocational high schools that has several skill competencies. One of them is the competence of Electrical Installation Engineering expertise which has the aim of producing graduates who are ready to work and competent in the field of electrical power installation. SMKN 1 Sumatera Barat certainly wants a good and optimal learning implementation so that it can support the school in achieving its goal of producing graduates who are ready to work and competent in their fields. However, in the competence of Electrical Power Engineering expertise, there are several learning processes that are not optimal. One of them is the learning process of Electric Motor Installation. Based on the latest curriculum, there is additional new material in the learning process of Electric Motor Installation, namely motor control using a speed drive device. However, schools do not yet have adequate special practicum equipment in the laboratory to support these learning materials. In addition, the competence of teachers in the field of controlling electric motors using the Varible Speed Drive device is also still low. This is one of the causes of the implementation of learning to be not optimal. Based on these problems, several actions were taken, namely making a VSD-based electric motor control trainer and carrying out training activities to increase teacher competence in the field of electric motor control using VSD. This activity is carried out in 4 stages of implementation, namely: (1) Planning stage; (2) Preparation Phase; (3) Implementation stage; (4) Evaluation and reporting stage. With this action, there is an increase in teacher competence in the field of electric motor control using VSD.